Nitric oxide-mediated alleviation of arsenic stress involving metalloid detoxification and physiological responses in rice (Oryza sativa L.). (15th March 2022) - Singh, Pradyumna Kumar; Chakrabarty, Debasis; Dwivedi, Sanjay; Kumar, Amit; Singh, Surendra Pratap; Sinam, Geetgovind; Niranjan, Abhishek; Singh, Poonam C.; Chatterjee, Sandipan; Majumdar, Dipanjali; Tiwari, Manish; Tripathi, Rudra Deo
Abstract: Rice is a staple crop, and food chain contamination of arsenic in rice grain possesses a serious health risk to billions of population. Arsenic stress negatively affects the rice growth, yield and quality of the grains. Nitric oxide (NO) is a major signaling molecule that may trigger various cellular responses in plants. The protective role of NO during arsenite (AsIII) stress and its relationship with plant physiological and metabolic responses is not explored in detail. Exogenous NO, supplemented through the roots in the form of sodium nitroprusside, has been shown to provide protection vis-à-vis AsIII toxicity. The NO-mediated variation in physiological traits such as stomatal density, size, chlorophyll content and photosynthetic rate maintained the growth of the rice plant during AsIII stress. Besides, NO exposure also enhanced the lignin content in the root, decreased total arsenic content and maintained the activities of antioxidant isoenzymes to reduce the ROS level essential for protecting from AsIII mediated oxidative damage in rice plants. Further, NO supplementation enhanced the GSH/GSSG ratio and PC/As molar ratio by modulating PC content to reduce arsenic toxicity. Further, NO-mediated modulation of the level of GA, IAA, SA, JA, amino acids and phenolic metabolites during AsIII stress appears to play a central role to cope up with AsIII toxicity. The study highlighted the role of NO in AsIII stress tolerance involving modulation of metalloid detoxification and physiological pathways in rice plants. Graphical abstract: Putative pathways for NO-mediated amelioration of AsIII toxicity. Nitric oxide positively regulated (directly/indirectly) the various metabolic pathways and physiological processes (represented by green lines) to inhibit oxidative stress (indicated by dotted red lines), and diminish AsIII toxicity (indicated by black line) in rice plants. Image 1 Highlights: The study explored the NO-mediated AsIII detoxification mechanism in rice plant. NO altered plant physiological responses to cope up with AsIII stress. NO enhanced lignin content, GSH/GSSG and PC/As molar ratio to reduce As accumulation. Variation in activities of antioxidant isoenzymes provided oxidative stress tolerance. NO modulated levels of plant growth regulators and phenolics during AsIII stress.